Size differences in the Dufour gland of Apis mellifera Linnaeus (Hymenoptera, Apidae) between and within the female castes - Abdalla, Fábio Camargo [UNESP]; Cruz-Landim, Carminda da [UNESP] (Sociedade Brasileira de Zoologia, 2001)
The Dufour gland is found closely associated with the sting apparatus of all hymenopteran females, playing multiple roles among bees. In Apis mellifera Linnaeus, 1758 the gland is connected to the dorsal vaginal wall and, in queens, it produces egg-marking pheromones. In workers the function of this gland is unknown, except by its capacity to mimic the queen secretion in egg-laying workers. In an attempt to understand the development and to substantiate the present knowledge about the Dufour gland in A. mellifera, a morphometric study of the gland between and within the female castes was made. Glands of workers and queens with different ages and life stages were dissected and measured with an ocular micrometer adapted to a stereoscope. The results showed that the Dufour gland is larger in queens than in workers, and that among workers, the gland is larger in egg-laying and foragers than it is in newly emerged and nurse workers. The larger size of the gland in egg-laying queens and workers is in accordance with its role in reproduction. In forager workers the larger size of the gland suggest that, as happens in some species of bees, the gland may participate in pheromone production for nest-mate or nest-entrance recognition.
Keywords: Apis mellifera; Dufour gland; exocrine glands